Pemberdayaan Masyarakat dalam Meningkatkan Ekonomi Nelayan di Danau Singkarak, Nagari Sumpur, Kecamatan Batipuh Selatan, Kabupaten Tanah Datar, Sumatera Barat - Rosni Rosni; Ryan Pramana; Nurul Ilmi; Putri Roito Lumbantobing; Anisa Niwanda; Putri Rahmadani; Ridho Amalan Saufi (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
Lake Singkarak is a tectonic lake that plays a vital role in supporting the economic life of the surrounding community, especially traditional fishermen in Nagari Sumpur. However, pressure on the ecosystem and the decline in the population of bilih fish pose a threat to the sustainability of fishermen's livelihoods. This study aims to analyze the form of community empowerment carried out and its impact on improving the fishermen's economy. The study was conducted through a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study showed that although an empowerment program had been carried out through assistance with fishing gear and PAP funds, its sustainability was not well maintained. Fishermen's income has not shown a significant increase, and tourism development has not fully touched their welfare. A more integrated strategy is needed between the fisheries and tourism sectors to realize sustainable empowerment.